PROGRAM EDU PARENTING DALAM MEWUJUDKAN KETERLIBATAN KELUARGA DALAM PENYELENGGARAAN PENDIDIKAN - La Jeti; Edison; amsaifil; Ida Mayasari; Laila Lamadi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
This research purpose to determine the quality of parents involvement in the delivery of education. This research was carried out in Pongkowulu Village, North Buton Regency. This community service used the Community based Research method with a qualitative approach. This research activity divide 3 stages, The first stage was Focus Group Discussion, Literature Review, and socialization were carried out by involving various parties, including the community service team, family, teachers, school principals, the community and the village government. Second Stage, Activities at this stage are assistance to socialize parenting program. The Community Service Team is directly involved in school activities involving parents of children, the community and the government related to the Parenting program, Parents Visits to school, child discipline, character building, healthy and comfortable environment programs. 3. Third stage, in the third stage the Community Service Team conducts interviews and observations. The results of this service show the awareness of the community, schools and village government, through educational activities held together. Parents begin to be involved in education, namely parenting style, character education in the family environment, socializing early childhood education program, children's learning patterns at home and joint evaluation of children's development